1987
DOI: 10.1212/wnl.37.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the Lehigh Valley

Abstract: Age-specific risk of recurrent stroke for various risk factors, calculated independently, was estimated using the first year of data from the Lehigh Valley Stroke Register. The register is based on a population of more than one-half million. Among the risk factors examined, the highest overall risk of recurrent stroke, 41.4, occurred with a history of at least one transient ischemic attack (TIA). After myocardial infarction (MI), the relative risk of a recurrent stroke was 8.0, while with all other heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 0 publications
1
28
0
3
Order By: Relevance
“…8 In that stroke cohort, hypertension was associated with a 4.5-fold increase in the risk of stroke recurrence (P<.001). The significance levels for the age-specific relative risks were 5.01 except for the risk among those aged <65 years (P=.05).…”
Section: Discussionmentioning
confidence: 77%
“…8 In that stroke cohort, hypertension was associated with a 4.5-fold increase in the risk of stroke recurrence (P<.001). The significance levels for the age-specific relative risks were 5.01 except for the risk among those aged <65 years (P=.05).…”
Section: Discussionmentioning
confidence: 77%
“…17 Only the MMSE was administered as a measure of cognitive function in the early period after the index ischemic stroke as part of the present study. We chose to include patients with a history of prior stroke or TIA in our analyses because previous studies have identified both prior stroke and TIA as predictors of recurrence 14,29 and we wished to examine their role in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…The increased risk of recurrent stroke due to diabetes ranges from 2.1 to 5.6 times that of nondiabetic patients (154,156) and is independent of glucose control during the interstroke period (163). The significance of these findings is underscored by the increased morbidity and mortality associated with recurrent stroke (164).…”
Section: Hypercoaguability Conferred By Diabetes -mentioning
confidence: 99%